Peran Psikologi Komunikasi dalam Pendidikan Islam - Liyana Rakhmawati (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2023)
Communication psychology is described as the science that explains, predicts, and controls mental events and behaviour in communication. One of the problems in education that is often overlooked is the lack of attention to psychological aspects in interactions between individuals, especially in the context of communication psychology. Educators and learners often experience boredom, laziness, and loss of motivation during the learning and working process. These psychological symptoms are commonly experienced by individuals in the process of learning or working, and to a certain degree, they will affect learning outcomes. The impact of these symptoms can create a crisis in the classroom, reduce motivation, and dampen the spirit of learning. In writing this article, the research method used is descriptive-qualitative. The descriptive-qualitative approach is applied to examine communication psychology in the context of Islamic education. The concept of communication psychology in the perspective of Islamic education must be upheld within the framework of the relationship between teachers and students that is full of affection, warmth, openness, freedom, honesty, sincerity, religious values, family atmosphere, and not in an atmosphere of power. Abstrak: Psikologi komunikasi digambarkan sebagai ilmu yang menjelaskan, meramalkan, dan mengendalikan peristiwa mental serta perilaku dalam komunikasi. Salah satu permasalahan dalam pendidikan yang sering diabaikan adalah kurangnya perhatian terhadap aspek psikologis dalam interaksi antar individu, khususnya dalam konteks psikologi komunikasi. Pendidik dan peserta didik sering mengalami kebosanan, malas, dan kehilangan motivasi selama proses belajar dan bekerja. Gejala-gejala psikologis ini umumnya dialami oleh individu dalam proses belajar atau bekerja, dan dalam tingkat tertentu, gejala ini akan memengaruhi hasil belajar. Dampak dari gejala-gejala ini bisa menciptakan krisis di dalam kelas, mengurangi motivasi, dan meredakan semangat belajar. Dalam penulisan artikel ini, metode penelitian yang digunakan adalah deskriptif-kualitatif. Pendekatan deskriptif-kualitatif diterapkan untuk mengkaji psikologi komunikasi dalam konteks pendidikan Islam. Konsep psikologi komunikasi dalam perspektif pendidikan Islam harus ditegakkan dalam kerangka hubungan antara guru dan murid yang penuh dengan kasih sayang, kehangatan, keterbukaan, kebebasan, kejujuran, kesungguhan dan ketulusan, nilai-nilai keagamaan, atmosfer kekeluargaan, dan bukan dalam suasana berkuasa.